2017
DOI: 10.1097/md.0000000000008315
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and diagnosis of chronic pulmonary aspergillosis in Chinese patients

Abstract: Chronic pulmonary aspergillosis (CPA) has recently been recognized as a significant global health burden. In China, the diagnosis of CPA is still unfamiliar to most doctors. The aim of this study was to demonstrate the clinical manifestations and diagnoses of CPA in China.A multidisciplinary team of doctors retrospectively screened 690 records of patients diagnosed with pulmonary aspergillosis from January 2000 to December 2016 at Peking Union Medical College Hospital, Beijing, China. Of these, 69 patients wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 23 publications
4
28
2
1
Order By: Relevance
“…The main systemic symptoms were cough, sputum production and fever, but the rate of chest pain was not high. The rate of haemoptysis (26.2%) was lower than other reports (49 and 63.8%) [6, 15]. One of the possible reasons is that the numbers of bronchiectasis and PTB, which contribute to haemoptysis, were small in our study.…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…The main systemic symptoms were cough, sputum production and fever, but the rate of chest pain was not high. The rate of haemoptysis (26.2%) was lower than other reports (49 and 63.8%) [6, 15]. One of the possible reasons is that the numbers of bronchiectasis and PTB, which contribute to haemoptysis, were small in our study.…”
Section: Discussioncontrasting
confidence: 79%
“…Nineteen of 42 CPA patients (including 17 inpatients and 2 outpatients) had pyrexia during the study period. The rate of fever (45.2%) was higher than other published papers reported (17.4 and 21%) [6, 15]. Among this group of CPA patients, 13 patients had other infections, 3 patients have connective tissue disease and 4 patients had pyrexia probably attributable to CPA.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Only two reports of Aspergillus nodules have been published in the literature. Hou et al reported that 3 of 69 patients with chronic pulmonary aspergillosis were diagnosed with Aspergillus nodules (5). Similarly, Muldoon et al reported 33 cases of Aspergillus nodules, 13 of which showed no evidence of tissue invasion upon pathological examination (6).…”
Section: Discussionmentioning
confidence: 99%
“…There were 36 males and 22 females, aged from 46 to 75 years (60.7 ± 14.6), and 37 IPA (63.8%) and 21 CPA cases (36.2%) were included. The CPA cases included 3 simple aspergilloma (SA), 10 chronic cavitary pulmonary aspergillosis (CCPA) and 8 subacute invasive aspergillosis (SAIA) cases [14]. Among these pulmonary aspergillosis patients, 7 patients (12.1%) has no other underlying diseases, 26 patients (44.8%) had chronic respiratory disease, and 15 patients (25.9%) had diabetes (Table 1).…”
Section: Patient Characteristicsmentioning
confidence: 99%